Hypothalamic-pituitary-adrenal axis and renin-angiotensin-aldosterone system in adulthood PTSD and childhood maltreatment history - Kakehi, Ryoko; Hori, Hiroaki; Yoshida, Fuyuko; Itoh, Mariko; Lin, Mingming; Niwa, Madoka; Narita, Megumi; Ino, Keiko; Imai, Risa; Sasayama, Daimei; Kamo, Toshiko; Kunugi, Hiroshi; et al. (Frontiers in Psychiatry, 2023)
Accumulated evidence shows that psychological trauma and posttraumatic stress disorder (PTSD) are associated with dysfunction in the hypothalamic-pituitary-adrenal (HPA) axis. Besides the HPA axis hormones, recent evidence suggests that the renin-angiotensin-aldosterone (RAA) system and genetic factors may be involved in trauma/PTSD as well as in HPA axis regulation. This study attempted to better understand the HPA axis function in relation to PTSD and childhood maltreatment by simultaneously examining RAA system and genetic polymorphisms of candidate genes. Here we studied 69 civilian women with PTSD and 107 healthy control women without DSM-IV-based traumatic experience. Childhood maltreatment history was assessed with the Childhood Trauma Questionnaire. PTSD severity was assessed with the Posttraumatic Diagnostic Scale. Functional disability was assessed with the Sheehan Disability Scale. HPA axis was examined by measuring blood levels of cortisol, adrenocorticotropic hormone, and dehydroepiandrosterone-sulphate (DHEA-S). RAA system was examined by measuring blood renin and aldosterone levels. The FKBP5 rs1360780 and CACNA1C rs1006737 polymorphisms were genotyped. No significant differences were seen between patients and controls in any of the 5 hormone levels. DHEA-S levels were significantly negatively correlated with overall PTSD severity (p = 0.003) and functional disability (p = 0.008). A 2-way analysis of variance with diagnostic groups and genotypes as fixed factors revealed that patients with the rs1006737 A-allele had significantly lower DHEA-S levels than patients with the GG genotype (p = 0.002) and controls with the A-allele (p = 0.006). Childhood maltreatment history in healthy individuals was not significantly correlated with any of the 5 hormone levels. These results were generally unchanged after controlling for the potentially confounding effect of age, depression, and anxiety. Our findings suggest that lower DHEA-S levels could indicate more severe subtype of PTSD, the association of which might be partly modified by the CACNA1C polymorphism.